In-silico analysis of Calcium Dependent Protein Kinase 6 of Cryptosporidium parvum through molecular modeling, docking, and dynamics simulation study. Issue 15 (2nd September 2021) - Dhal, Ajit Kumar; Pani, Alok; Yun, Soon-IL; Mahapatra, Rajani Kanta
Abstract: Calcium Dependent Protein Kinases are found in the Apicomplexan, algae, and plants; however, they are not reported in vertebrates and are regarded as excellent drug targets for pharmaceutical interventions. Calcium Dependent Protein Kinases of Cryptosporidium are probably involved in the regulation of invasion and egress process during the infection of the host cells. The previous study reported that after the Calcium Dependent Protein Kinase 1 gene, Calcium Dependent Protein Kinase 6 of Cryptosporidium parvum is expressed in all stages of the parasite (merozoites/schizonts as well as sexual stages) at a comparable level and makes it as a valid drug target. In this study, an attempt is made to address the similarity in sequences and phylogenetic study of Calcium Dependent Protein Kinase 6 (CDPK6) among Calcium Dependent Protein Kinases of Apicomplexans. Further, the three-dimensional structure determination of CDPK6 of C. parvum was performed through a molecular modeling approach followed by virtual screening of small-molecule inhibitors from different datasets. The best inhibitor from Tres Cantos Antimalarial Set with ID 11730 reported a binding affinity of −8.2 kcal/mol against CDPK6 of C. parvum . Furthermore, the reliability of the binding mode of the inhibitor is validated through a complex molecular dynamics simulation study for a time interval of 100 ns. The simulation study advocates that the inhibitor Tres Cantos Antimalarial Set_11730 formed a stable interaction with the predicted active site residues and can be considered for industrial pharmaceutical research in future. Communicated by Ramaswamy H. Sarma